STATE FOREST FUND OF REPUBLIC OF INGUSHETIA - L. D. Oligova (Юг России: экология, развитие)
The article presents the state forest fund of the Republic of Ingushetia. Woods of Ingushetia perform riparian, soil protection and other functions. For this category of protection forests classified as forests, along rivers and their tributaries. Age of main forest species of the forest fund of the republic is 160 years old, at the age of razbezhka tree species is 20 years.